Characterization of a traditional ripened cheese, Kurdish Kope: Lipolysis, lactate metabolism, the release profile of volatile compounds, and correlations with sensory characteristics. Issue 8 (19th July 2021) - Esmaeilzadeh, Peiman; Ehsani, Mohammad Reza; Mizani, Maryam; Givianrad, Mohammad Hadi
Abstract : Abstract: Kope cheese has been characterized based on gross chemical composition, free fatty acids (FFAs), organic acids (OAs), volatile compounds (VCs), and sensory attributes (SAs) during 187 days of the ripening period. C16:0, C18:1cisΔ9, and C14:0 were the most abundant FFAs. Lactic and acetic acids were the most prevalent OAs affecting sensory properties. principal component analysis (PCA) indicated that butanoic acid, butyl hexanoate, and 2, 3‐butanediol were as key VCs. Protein contents, pH (based on FFA and OA), salt in the moisture (S/M), and water activity ( aw ) (based on VC and SA) were highly correlated with PC2, resulted in two distinct groups. Based on lipolysis and glycolysis studies, early‐ripened cheese samples showed lipolysis and lactate metabolism more intensely compared to medium and old‐ripened ones. Based on the data of VC and SA, the samples may be classified into three groups: (1) early‐ripened cheeses with a salty taste, waxy to cheesy odor, and rubbery texture, (2) medium‐ripened cheese with a sweet taste and cheesy odor, and (3) old‐ripened cheese with a bitter taste, cheesy to pungent odor, a firm and fragile texture. Textural attributes were highly correlated with proteolysis indices and pH. The results of sensory desirability indicated a significant correlation with pungency, bitterness, and OAs. The cheese samples ripened on the day 127 were selected as the most desirable product. Ripening time had a significant effect on the chemical composition, especially on S/M, pH, and aw parameters, which determine the pattern as well as the intensity of biochemical pathways and the final sensory attributes. Practical Application: The current study intends to characterize and develop a standardized procedure for producing a traditional cheese called "Kope cheese" by determining the appropriate duration time for the ripening process, determining the main chemical/biochemical compounds that are highly correlated with its unique flavor and texture and distinguishing the key processing factors (such as curd salting, pH values during brining) that have to be altered or controlled carefully during the manufacturing process. The data would help cheese manufacturers determine the optimum time of ripening in order to achieve the best flavor and texture attributes in the final product.